المشروع البيداغوجي في شعر السياب - كريم, أ.د.ظاهر لطيف; علي, د.ژینۆ عبدالله (Sulaimani Journal for Humanities, 2021)
This research pedagogical process in Al-Sayyab s poetry. This research confirms the educational influences of the texts on the readers due to the aims and function of pedagogical process which is the most commonly understood as the approach to teaching and learning. Pedagogy is the method and practice of teaching when the poets like Al-Sayyab plans atext they will consider different ways to deliver the contents. In this case the pedagogical process comes to educational corrections in particular in the middle east societies which they could not easily understand the real meaning of the texts. This is because of luck information's of educational position of affaires. On the other hand the pedagogical process creates an educated readers this type of readers can manage to connect the mutual actions.